The value of walking: a systematic review on mobility and healthcare costs - Wohlrab, Martin; Klenk, Jochen; Delgado-Ortiz, Laura; Chambers, Michael; Rochester, Lynn; Zuchowski, Matthias; Schwab, Matthias; Becker, Clemens; Jaeger, Simon U. (European review of aging and physical activity, 2022)
The ability to walk is an important indicator of general health and mobility deficits have wide-ranging economic implications. We undertook a systematic review to elucidate the impact of walking parameters on health care costs.
Gesehen am 09.02.2023